Respuesta :
Answer:
y+6=3/2(x+9)
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(6-(-6))/(-1-(-9))
m=(6+6)/(-1+9)
m=12/8
simplify
m=3/2
y-(-6)=3/2(x-(-9))
y+6=3/2(x+9)
The equation of the line is y + 6 = 3/2(x+9).
What is the slope of the line?
The slope of the line is defined as the angle of the line. It is denoted by m
Slope m = (y₂ - y₁)/(x₂ -x₁ )
Consider two points on a line—Point 1 and Point 2. Point 1 has coordinates (x₁,y₁) and Point 2 has coordinates (x₂, y₂)
Given,
The line passes through the points (−9,−6) and (−1,6)
Let
x₁ = -9, y₁ = -6
x₂ = -1, y₂ = 6
∵ Slope m = (y₂ - y₁)/(x₂ -x₁ )
Substitute values in the formula
m = (6-(-6))/(-1-(-9))
m = (6+6)/(-1+9)
m = 12/8
m = 3/2
Let the line (y - y₁) = m(x -x₁ )
Substitute the values in the equation,
So, y-(-6) = 3/2(x-(-9))
y + 6 = 3/2(x+9)
Hence, the equation of the line is y + 6 = 3/2(x+9).
Learn more about Slope of Line here:
brainly.com/question/14511992
#SPJ2